Application of Regulatory Cell Death in Cancer: Based on Targeted Therapy and Immunotherapy - Qi, Xiaochen; Li, Quanlin; Che, Xiangyu; Wang, Qifei; Wu, Guangzhen (Frontiers in Immunology, 2022)
The development of cancer treatment methods is changing with each passing day. For common cancers, our treatment methods are still based on conventional treatment methods such as chemotherapy and radiotherapy and targeted drug therapy. Nevertheless, the emergence of tumor resistance has a negative impact on treatment. Regulated cell death (RCD) is a gene-regulated mode of cell death. After receiving specific signal transduction, cells change their physical and chemical properties and extracellular microenvironment, resulting in structural destruction and decomposition. As research accumulates, we now know that by precisely inducing specific cell death patterns we can kill cancer cells and treat cancer with less collateral damage than other treatments. With the further study of RCD, many newly discovered types of RCD are thought to be useful for cancer treatment. However, some experimental results suggest that some RCDs are not sensitive to cancer cell death, and some may even promote cancer progression. This review will summarize the discovered types of RCDs, review their clinical efficacy in cancer treatment, explore their anticancer mechanisms, and discuss the feasibility of some newly discovered RCDs for cancer treatment in combination with the immune and tumor microenvironment.